Ca2+ Permeable AMPA Channels in Diseases of the Nervous System - Weiss, John H. (Frontiers in Molecular Neuroscience, 2011)
Since the discovery and molecular characterization of Ca2+ permeable AMPA channels just over 2 decades ago, a large body of evidence has accumulated implicating contributions of these unusual glutamate activated channels to selective neurodegeneration in certain conditions, including ischemia and ALS. Factors likely involved in their contributions to disease include their distinct patterns of expression in certain neuronal populations, their upregulation via various mechanisms in response to disease associated stresses, and their high permeability to Zn2+ as well as to Ca2+. However, full characterization of their contributions to certain diseases as well as development of therapeutics has been limited by the lack of selective and bioavailable blockers of these channels that can be employed in animals or humans. This review summarizes some of the clues that have emerged over recent years to the contributions of these channels in disease.